Immune Complex-Type Deposits in the Fischer-344 to Lewis Rat Model of Renal Transplantation and a Subset of Human Transplant Glomerulopathy - Grau, Veronika; Zeuschner, Philip; Immenschuh, Stephan; Bockmeyer, Clemens Luitpold; Zell, Stefanie; Wittig, Juliane; Saeuberlich, Karen; Abbas, Mahmoud; Padberg, Winfried; Meyer-Schwesinger, Catherine; Von Brandenstein, Melanie; Schlosser, Monika; et al. (Transplantation, 2016)
Antibody-mediated rejection is a leading cause for renal transplant loss. Rodent models are useful to dissect pathomechanisms and to develop treatment strategies. Although used for decades as a model, glomerular histopathological findings of Fischer-344 kidneys transplanted into Lewis rats have never been comprehensively described.Kidneys from Fischer-344 rats were transplanted into Lewis rats as life-sustaining allografts without immunosuppression. Lewis isografts and normal Fischer-344 kidneys served as controls. Grafts were harvested at 9 days, 6 and 26 weeks. Histopathological examination included light microscopy, immunohistochemistry, and morphometry. Findings were compared with 51 human biopsies with transplant glomerulopathy.Most glomerular findings in rat allografts resembled human acute and chronic antibody-mediated rejection with glomerulitis, microthrombosis, microaneurysms, glomerular hypertrophy, podocyte loss, glomerular basement membrane splitting, and secondary focal and segmental glomerulosclerosis. In line with previous reports on nonendothelial antigens, glomerular immunoglobulin and C4d deposition was mostly nonendothelial. Only in 26-week allografts, we found mesangial and subendothelial immune complex-type electron-dense deposits. Similar deposits were found in 8 of 51 human biopsies with transplant glomerulopathy after rigorous exclusion of immune complexes of other cause, particularly recurrent glomerulonephritis and hepatitis C.Thus, our model closely reflects the glomerular changes of acute antibody-mediated rejection in humans and of a special subset of human transplant glomerulopathy. The significance of alloimmune immune complex-type deposits in human transplants deserves further investigation.
EVALuna2:25520